Implementasi Algoritma A* (Star) dengan Graf untuk Menentukan Rute Terpendek Distributor Kopi - Putra, I Putu Andi Wiratama; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
In this research, the A Star algorithm is employed to find the most efficient route for goods distribution. Distributors encounter challenges in ensuring timely deliveries due to the presence of multiple destinations spread across different regions. Congestion further adds to the complexity of determining the shortest path. The A Star algorithm utilizes the distance-plus-cost function to prioritize the order of visiting points. This study utilizes primary data, comprising five shop locations in the Tabanan city, as nodes and incorporates the distances between the shops. The implemented program utilizes the A Star algorithm to compute the shortest route and present the path along with its corresponding distance. The objective of this research is to attain the shortestroute and calculate the distance covered for the coffee distributor.